Optimum Policy Domains in an Interdependent World - Michael P. Evers (University of Bonn, Bonn Graduate School of Economics (BGSE), 2007)
In this paper, I argue that international policy coordination requires to include both monetary as well as fiscal policy because both sides include policy instruments that allow the strategic manipulation of the country's terms of trade. Hence, the coordination of one part of national macroeconomic policies through an international agreement still leaves room for national authorities to still unilaterally manipulate the terms of trade by means of different policy instruments. In a simple and tractable dynamic stochastic two-country sticky-wage model in line with the recent New Open Economy Macroeconomics it is demonstrated that potential gains from international policy coordination are squandered if policymakers only cooperate on monetary policy. Moreover, by letting the fiscal policy instruments be chosen non-cooperatively, monetary policy coordination might even create welfare losses as compared to no macroeconomic policy coordination at all.
Keywords: F41; F42; E62; E63; 330; International Policy Coordination; General Short-Run Monetary Policy; Distorting Fiscal Policy; Beggar-Thy-Neighbor; New Open Economy Macroeconomics; Geldpolitik; Finanzpolitik; Internationale wirtschaftspolitische Koordination; Terms of Trade; Konjunkturzusammenhang; Wohlfahrtseffekt; Neue Makroökonomik offener Volkswirtschaften; Theorie